Knowledge concepts in competence-based VET research : perspectives on cognitivist and social-constructivist approaches - Dietzen, Agnes [Verfasser] (My University, 2017)
"Recent positions in competence-based VET research differ in their views on what types of knowledge are addressed in competence-based curricula as well as on the way different types of knowledge are valued in competence assessments. The debate is rooted in different theoretical and epistemic positions on concepts of competence: a holistic approach to competence based mainly on a socio-constructivist epistemic position, e.g. educational (Bildung) and anthropological-oriented social theories on action and professional practice. The competing perspective is based on psychological-cognitivist and action theories and underlies the research on empirical modelling and competence diagnostic in VET. Within this perspective, competencies are defined as 'acquired cognitive dispositions of performance'. This chapter analyses these different concepts of competence with regard to their respective standpoints on the role and types of knowledge involved. The line of reasoning starts with a preliminary didactic debate on casuistic learning versus systematic subject learning. This debate makes visible different positions on the role of knowledge, which are then continued in the debate on competence research and assessments. Central assumptions of a social-constructive and cognitivist-related perspective on competence are discussed in the following sections. The social-constructive perspective will be contained by the tacit knowing approach, as propounded in the German-language vocational pedagogy debate. By way of contrast, the cognitive perspective will be analysed by focusing on theories on action (regulation) and social cognition as central strands within the competence approach. The chapter concludes with the question as to whether these conceptual approaches are convergent or divergent." (Authors' abstract, BIBB-Doku)
Keywords: T 2.1 Bildungstheorien; Bildungstheorie; Kompetenz; Kompetenzbegriff